Age-Related Changes in Gustatory, Homeostatic, Reward, and Memory Processing of Sweet Taste in the Metabolic Syndrome: An fMRI Study. (March 2017) - Jacobson, Aaron; Green, Erin; Haase, Lori; Szajer, Jacquelyn; Murphy, Claire
Age affects the human taste system at peripheral and central levels. Metabolic syndrome is a constellation of risk factors (e.g., abdominal obesity and hypertension) that co-occur, increase with age, and heighten risk for cardiovascular disease, diabetes, and cognitive decline. Little is known about how age, metabolic syndrome, and hunger state interact to influence how the brain processes information about taste. We investigated brain activation during the hedonic evaluation of a pleasant, nutritive stimulus (sucrose) within regions critical for taste, homeostatic energy regulation, and reward, as a function of the interactions among age, metabolic syndrome, and hunger condition. We scanned young and elderly adults, half with risk factors associated with metabolic syndrome twice: Once fasted overnight and once after a preload. Functional magnetic resonance imaging data indicated significant effects of age as well as interactive effects with metabolic syndrome and hunger condition. Age-related differences in activation were dependent on the hunger state in regions critical for homoeostatic energy regulation and basic as well as higher order sensory processing and integration. The effects of age and metabolic syndrome on activation in the insula, orbital frontal cortex, caudate, and the hypothalamus may have particularly important implications for taste processing, energy regulation, and dietary choices.